Design and Development of an Autoinjector Tracking Device to Integrate with Emergency Service - Maqungu, Qhamani (Department of Human Biology, 2025)
Anaphylaxis is a life-threatening allergic reaction that requires treatment by prompt injection of epinephrine typically via epinephrine autoinjectors (EAI). An immediate visit to the emergency room (ER) to avoid possible relapse is necessary. Studies have shown that the effectiveness of epinephrine decreases with the prolonged delay of injection after symptoms onset. Many patients get hospitalised or die due to delayed epinephrine injection or unavailability of the EAI devices when it is mostly needed. Some of the reasons for unavailability at the incident site is usually associated with patients forgetting to carry their EAI. Some patients hesitated to administer epinephrine, resulting to a relapse hours later and while some did not seek further monitoring from a trained clinician after administering epinephrine. This study aimed at designing and developing an EAI tracking device to send reminder notifications to patients when they are located ten meters away from their EAI, and to alert emergency medical services (EMS) via SMS, containing location, when the patient is experiencing anaphylaxis. Using Impulse Biomedical's EAI ZibiPen device as a use case, a Bluetooth low energy (BLE) tracking device named GuardAin, was developed and linked to an Android mobile phone application. A pilot case-based study aimed at validating the accuracy of the notification alert algorithm in threedimensional directions was conducted at the Impulse Biomedical offices in the Western Cape. The test conditions were phone in hand and phone in pocket. The distance algorithm was validated using a ttest. The location accuracy from the emergency alert SMS was validated and compared to Google Maps. A total of 80 notification alert tracking tests were conducted. Forty tests were conducted for the horizontal direction test resulting in the detection of ten meters with an average of 10.7 meters. Forty vertical tests resulted in poor detection of a ten-meter distance. However, consistency in detecting three meters was observed with an average of 3.3 meters. The 3.3 meters was the average floor height in the building. Eight locations were selected as the choice of emergency trigger locations. The emergency alert locations were accurately detected within a 50-meter radius. The algorithm was found to be fairly accurate in detecting 10 meters and could serve as a reliable reminder for EAI adherence. However, walking pace determined how far past ten meters the notifications were sent. SMS emergency alerts were found useful to detect EAI usage and accurately relaying patient location to EMS and other emergency contacts. Future works include investigating the usability of the reminder system, and practicality of the emergency services alert system. Additionally, the tracking algorithm to be validated with different Android mobile devices.